Criminal tax - Requenes, J. Isabel García (Seven Editora, 2024)
After the easy and rapid production of synthetic drugs increased and some U.S. states legalized marijuana use, drug trafficking ceased to be the main source of income for criminal organizations in Mexico. This business began to become unsustainable for the Mexican cartels, which soon led them to venture into a more lucrative business. Organized crime has diversified its criminal activities, mainly through extortion through the collection of derecho de piso or "criminal tax" from all types of businesses. In this way, criminal groups have found in extortion not only a way to regulate everything that can produce capital, but also to recover the profits that the decline in the trafficking of plant-based drugs left them after the increase in the consumption and trafficking of synthetic drugs. Criminal groups go to businesses and establishments to demand, under threats, that the owners pay a certain amount of money periodically. The goal is to offer "protection" from the threat of harming the business or the person who owns the establishment. The extortionist presents himself as "the protector", while the criminal can use violence if the fee is not paid. "For criminals, there is no longer any formal or informal activity, line of business or business that they do not extort, in addition to also controlling entire markets in the country for products such as chicken, tortillas, eggs, construction materials and many other activities that can no longer operate calmly and legally if they do not pay fees and taxes to criminals. And those who refuse to pay outright are murdered, see their businesses burn down or, the bravest, prefer to close their family businesses, companies or grape harvests, so as not to have to pay taxes to organized crime, in addition to those they already pay to the government." (García Soto, 2024) In Mexico, organized crime has determined that anyone who produces something, sells anything or trades any type of goods and services, can be charged extortion amounts ranging from 50,000 to 1 million pesos per month, no matter if they are a street vendor, a small family business, or a small family business. a medium-sized company or even a large supermarket chain. It is suspected that most of the intentional homicides registered in the country are linked to the collection of floor fees in bars, grocery stores, street vendors, cattle ranchers, farmers, transporters, butchers, gas stations and bakeries. Mexicans are paying double taxation: on the one hand, that of governments, and on the other, that of organized crime. At least five different fees charged by organized crime have been identified: derecho de piso, derecho de transit, extortion telefónica, extortion on the highway and family security. As a result, extortion has become their main source of financing. The crime of extortion has high levels of black figures, that is, it is not reported to state prosecutors’ offices or prosecutors’ offices due to the victims’ fear of reprisals from criminals dedicated to extortion in the country in different modalities. DOI:https://doi.org/10.56238/sevened2024.007-086